Innate gut microbiota predisposes to high alcohol consumption. (28th January 2021) - Ezquer, Fernando; Quintanilla, Maria Elena; Moya‐Flores, Francisco; Morales, Paola; Munita, José Manuel; Olivares, Belén; Landskron, Glauben; Hermoso, Marcela A.; Ezquer, Marcelo; Herrera‐Marschitz, Mario; Israel, Yedy
Abstract: Gut microbiota is known to be transferred from the mother to their offspring. This study determines whether the innate microbiota of rats selectively bred for generations as high alcohol drinkers play a role in their alcohol intake. Wistar‐derived high‐drinker UChB rats (intake 10‐g ethanol/kg/day) administered nonabsorbable oral antibiotics before allowing access to alcohol, reducing their voluntary ethanol intake by 70%, an inhibition that remained after the antibiotic administration was discontinued. Oral administration of Lactobacillus rhamnosus Gorbach–Goldin (GG) induced the synthesis of FGF21, a vagal β‐Klotho receptor agonist, and partially re‐invoked a mechanism that reduces alcohol intake. The vagus nerve constitutes the main axis transferring gut microbiota information to the brain ("microbiota‐gut‐brain" axis). Bilateral vagotomy inhibited rat alcohol intake by 75%. Neither antibiotic treatment nor vagotomy affected total fluid intake. A microbiota‐mediated marked inflammatory environment was observed in the gut of ethanol‐naïve high‐drinker rats, as gene expression of proinflammatory cytokines (TNF‐α; IL‐6; IL‐1β) was significantly reduced by nonabsorbable antibiotic administration. Gut cytokines are known to activate the vagus nerve, while vagal activation induces pro‐rewarding effects in nucleus accumbens. Both alcoholics and alcohol‐preferring rats share a marked preference for sweet tastes—likely an evolutionary trait to seek sweet fermented fruits. Saccharin intake by UChB rats was inhibited by 75%–85% by vagotomy or oral antibiotic administration, despite saccharin‐induced polydipsia. Overall, data indicate that the mechanisms that normally curtail heavy drinking are inhibited in alcohol‐preferring animals and inform a gut microbiota origin. Whether it applies to other mammals and humans merits further investigation. Abstract : Alcohol use disorders are accompanied by gut microbiota changes that predict alcohol craving; further, animals transplanted with feces from alcoholics increase their preference for alcohol. This work shows that inborn microbiota is largely responsible for alcohol preference of rats selectively bred for their high alcohol intake. Proinflammatory gut microbiota communicates with brain via vagus nerve, enhancing drug hedonic effect. This study shows that both oral antibiotic administration and vagotomy virtually suppressed the high alcohol intake of the Wistar‐derived UChB rat.